2020
DOI: 10.1175/jcli-d-20-0084.1
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and Natural Contributions to the Lengthening of the Southern Hemisphere Summer Season

Abstract: This study provides the first quantitative assessment of observed long-term changes in summer season timing and length in the Southern Hemisphere (SH) and its sub-regions over the past 60 years, enabling a global completeness by complimenting such characteristics previously reported for the Northern Hemisphere (NH). Using an objective algorithm based on temperature indices, relative measures of summer onset, withdrawal, and duration are determined at each land location over the period 1953–2012. Significant wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…(2020) indicated that the surface warming induced by greenhouse gases and anthropogenic aerosols is stronger in winter than in summer in the Northern Hemisphere. Temperature seasonality changes caused by anthropogenic forcing can also be clearly detected in other regions, such as in the Southern Hemisphere (Park et al ., 2018; Santer et al ., 2018; Weller et al ., 2020), China (Qian and Zhang, 2019), and the Tibetan Plateau (Duan et al ., 2017). Besides anthropogenic forcing, natural variability also affects temperature seasonality (Tesouro et al ., 2005; Stine et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) indicated that the surface warming induced by greenhouse gases and anthropogenic aerosols is stronger in winter than in summer in the Northern Hemisphere. Temperature seasonality changes caused by anthropogenic forcing can also be clearly detected in other regions, such as in the Southern Hemisphere (Park et al ., 2018; Santer et al ., 2018; Weller et al ., 2020), China (Qian and Zhang, 2019), and the Tibetan Plateau (Duan et al ., 2017). Besides anthropogenic forcing, natural variability also affects temperature seasonality (Tesouro et al ., 2005; Stine et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a trend toward decreased amplitude and advanced phase in the Northern Hemisphere average temperature during the twentieth century has been found (e.g., Mann and Park, 1996; Wallace and Osborn, 2002; Stine et al ., 2009). Statistically significant lengthening of the summer season was presented across the majority of land regions in the Southern Hemisphere during 1953–2012 (Weller et al ., 2020). Cassou and Cattiaux (2016) showed an earlier onset of summer by approximately 10 days over Europe between the 1960s and 2000s.…”
Section: Introductionmentioning
confidence: 99%
“…The extension of summer and the shortening of winter have been detected around the globe in the past half‐century (e.g., Schwartz et al ., 2006; Dong et al ., 2010; Peña‐Ortiz et al ., 2015; Allen and Sheridan, 2016; Park et al ., 2018; Weller et al ., 2020; Wang et al ., 2021a; 2021b) and will continue and even strengthen in the future according to model projections (Hochman et al ., 2018; Wang et al ., 2021a). The changes in season lengths and onsets in China have also received some attention (e.g., Dong et al ., 2010; Yu et al ., 2010; Yan et al ., 2011) and have been found to be generally similar to hemisphere‐scale results.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the summer season timing and duration is important in line with the recent increases in heat wave events that caused tremendous damages across the globe (Pfleiderer et al., 2019; Zscheischler & Seneviratne, 2017). The observed summer season has lengthened over both hemispheres during the recent decades, which has been attributed to anthropogenic greenhouse warming (Allen & Sheridan, 2016; Park et al., 2018; Peña‐Ortiz et al., 2015; Weller et al., 2020). As the upcoming twenty‐first century faces unprecedented warming conditions (Diffenbaugh & Scherer, 2011; Masson‐Delmotte et al., 2021), summer season will be further expanded (Park et al., 2022; Ruosteenoja et al., 2019; J. Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%